2019
DOI: 10.1186/s12939-019-1104-1
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of cultural competence in ethnic minority consumer engagement? An analysis in community healthcare

Abstract: BackgroundEffective patient engagement has been associated with high quality health care. There is a dearth of evidence around effective engagement with consumers from ethnic minority backgrounds; specifically in relation to the role of cultural competence amongst healthcare professionals in effective engagement with consumers from ethnic minority backgrounds. To address this knowledge gap, we analysed the role of cultural competence in the consumer engagement approaches taken by community healthcare professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…The role of bilingual healthcare staff in positively addressing language and culture was identified in a number of studies [51,58,64]. Bilingual staff may improve communication and are highly valued by organisations and patients alike as they speak the patients' language and understand their culture context [25,77]. The evidence from the present review suggests that use of interpretation through a range of means is valuable in addressing some patient safety issues but may also leads to others.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The role of bilingual healthcare staff in positively addressing language and culture was identified in a number of studies [51,58,64]. Bilingual staff may improve communication and are highly valued by organisations and patients alike as they speak the patients' language and understand their culture context [25,77]. The evidence from the present review suggests that use of interpretation through a range of means is valuable in addressing some patient safety issues but may also leads to others.…”
Section: Discussionmentioning
confidence: 78%
“…The Australian Commission of Safety and Quality in Health Care (ACSQHC) identifies consumer engagement strategies as central to improved health and healthcare safety outcomes for consumers [21,81]. Recent studies has also highlighted the role of patient and carer engagement among ethnic minority populations as critical for enhanced healthcare [25,77]. Consumers can act as safety buffer by identifying when the care is not adequate or unsafe [82].…”
Section: Discussionmentioning
confidence: 99%
“…Family caregivers (especially the older generation) may also feel uncomfortable discussing the patient's condition with the medical staff. The important role should have cultural competence of healthcare workers [44] Study 1 demonstrated that family caregivers of the "Arab" older adults were more likely to stay during the night than the two other ethno-cultural groups. This could be related to the Arabic cultural tradition of respect for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence supports that having caregivers, providers, researchers, educators, and leaders from within the population and communities being served is important. Harrison et al (2019) reported that ethnic minority populations experience obstacles when engaging with health care systems. In addition, it is of the upmost importance to embed cultural competence strategies into health systems and services to ensure professionals have knowledge and skills to engage individuals from a culture standpoint.…”
Section: Culturally Congruent Health Care For Aa/blacksmentioning
confidence: 99%